Recovery in water polo: how much do we have to know? A systematic review - Barrenetxea-Garcia, J.; Murua-Ruiz, A.; Mielgo-Ayuso, J.; Nuell, S.; Villarreal, E. (Journal of Exercise Rehabilitation, 2022)
Water polo (WP) is a high-intensity intermittent aquatic sport, with a predominance of swimming skills and nonswimming activities and incomplete recovery periods. Consequently, recovery after exercise is a fundamental part of sports performance. The main purpose of this systematic review was to evaluate the effects of different recovery strategies in WP performance. The studies were found by searching in the databases of PubMed, Web of Science, and Scopus. Methodological quality and risk of bias were assessed in accordance with the Cochrane Collaboration Guidelines samples. A summary of results including five studies was followed. The results show that supplementation with cherry juice before training does not imply improvements in recovery; the full-body photobiomodulation therapy reduces muscle damage; reducing training load during the season increased the natural logarithm of the root mean square of successive differences and perceived state of recovery, and the heart rate variability stabilizes and could progressively increase at the end of a tournament; and when an increase in internal training load is less than 60%-70% autonomic cardiac disturbances during preseason training do not occur. Recovery in WP is a very limited field of study that needs future research in active recovery, hydrotherapy, massage, rest and sleep to help coaches formulate recommendations.